Preparation of 2-propanol dehydrogenation catalysts for chemical heat pump system - Lee, H; Song, HK; Na, BK (CHEMICAL SOC JAPAN, 2000)
2-Propanol dehydrogenation catalysts were prepared using three types of preparation methods. The catalytic activities of these catalysts were compared through reaction experiments. A Ru catalyst, prepared by an incipient-wetness method followed by NaBH4 reduction, had the predominant reaction rate, and a Pt catalyst, prepared by an incipient-wetness method with H-2 reduction at 400 degrees C, showed high activity. The Ru catalysts with high temperature reduction and Pt catalysts with NaBH4 reduction showed negligible reaction rates; Also, a catalyst supported on activated carbon had a better activity than that on alumina. The Ru on activated carbon was proper for a chemical heat-pump system because of higher activity and a lower reduction temperature than the Pt catalyst.
Keywords: HYDROGENATION; ACETONE